IMPLEMENTATION OF ELECTRONIC – DEWEY DECIMAL CLASSIFICATION EDITION 23 IN THE LAMPUNG PROVINCE LEGAL DOCUMENTATION & INFORMATION NETWORK LIBRARY (JDIH) - Nedo Bangsawan; Mezan El Khaeri Kesuma; Irva Yunita; Muhamad Bisri Mustofa (Unversitas Muhammadiyah Mataram, 2025)
The Legal Documentation and Information Network Library (JDIH) of Lampung Province faced challenges in managing legal document classification manually, which often resulted in inefficiency and errors. The library began implementing the 23rd edition of the Electronic Dewey Decimal Classification (e-DDC) system in May 2023 to address this issue. This study aims to examine the implementation of e-DDC in improving the efficiency of document classification in the library. A qualitative research approach was employed using a case study method. Data were collected through in-depth interviews with four library staff members and six users, supported by observations and documentation. The findings reveal that the implementation of e-DDC positively impacted collection management, including faster classification processes, improved accuracy, and effective integration with the library management system (SLiMS). Users also reported easier access to and retrieval of legal materials. However, several obstacles were identified, such as the initial lack of understanding among staff, limited technological infrastructure, challenges in transitioning from a manual to a digital system, and insufficient user orientation regarding the e-DDC system. Key findings indicate that successful implementation is supported by adequate staff training, strong managerial support, and the availability of appropriate technological tools. On the other hand, additional strategies are needed, such as providing user guidance and improving technological infrastructure. In conclusion, the 23rd edition of e-DDC has proven effective in enhancing the efficiency and accessibility of legal information, although continuous improvements are required to optimize its use.